Effects of plyometric training on physical fitness in adolescent and adult female team sport athletes: a systematic review and meta-analysis - Lin, G.; Zhang, R.; Wu, K.; Deng, B.; Shi, Y.; Huang, W.; He, J.; Sun, J. (Frontiers in Physiology, 2025)
Objective: This study aimed to investigate the effects of plyometric training (PT) on various physical fitness outcomes in adolescent and adult female team sport athletes.